UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK MELALUI PERMAINAN SAINS - Endang Wahyuni (Lembaga Penerbitan dan Publikasi Ilmiah (LPPI) Universitas Muhamamdiyah Palopo, 2021)
The research objective was to determine how the efforts to improve children's cognitive abilities through science games in Group B TK Tunas Harapan Kota Palopo. This type of research in this study is a type of Classroom Action Research (PTK). Classroom Action Research carried out four stages of planning (planning); Action or action (acting); Observation (observing: Reflection). The research location of TK Tunas Harapan was located on Jl Benteng Raya, Benteng, Kec. Wara Timur, Palopo City, South Sulawesi Province. Data analysis techniques were carried out to obtain the average and percentage of children's cognitive abilities towards science games The results of the study, as a whole the results of the students' acquisition show that trying and telling about what happened 75% are declared Completed, while revealing cause and effect 59% are declared Not Completed and revealing the origin of something happening 68% are declared Not Completed. due to the increase in the average cycle I to Cycle II of 50%. Through games of science can improve children's cognitive abilities in Group B Kindergarten Tunas Harapan Palopo City.